2010
DOI: 10.1111/j.1865-1682.2010.01164.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Global Warming and Evolution of Nucleoproteins from Influenza A Viruses since 1918

Abstract: Global warming affects not only the environment where we live, but also all living species to different degree, including influenza A virus. We recently conducted several studies on the possible impact of global warming on the protein families of influenza A virus. More studies are needed in order to have a full picture of the impact of global warming on living organisms, especially its effect on viruses. In this study, we correlate trends in global warming with evolution of the nucleoprotein from influenza A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Another climatic factor was the minimum temperature, which is slowly rising due to the influence of human activities. In recent years, multiple studies have proposed that global warming will likely influence the life of all living species, including the evolution of influenza A virus [20,21]. Furthermore, Yan et al found that global warming affects many different levels of biological evolution; even intracellular proteins are subject to global warming [22].…”
Section: Discussionmentioning
confidence: 99%
“…Another climatic factor was the minimum temperature, which is slowly rising due to the influence of human activities. In recent years, multiple studies have proposed that global warming will likely influence the life of all living species, including the evolution of influenza A virus [20,21]. Furthermore, Yan et al found that global warming affects many different levels of biological evolution; even intracellular proteins are subject to global warming [22].…”
Section: Discussionmentioning
confidence: 99%
“…These include the uncertainty around the viral species' pathogenesis and its transmissibility mechanics. The role of urbanization [ 1 ], globalization [ 2 ], and global warming [ 3 ] in global pandemics still needs to be clarified, as is the part of social media on information spread and individual behaviors [ 4 , 5 ]. Hence, the reality is evidenced by the rates at which emerging infectious disease [ 6 ] gets transmitted on a large scale within days to cause global threats [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…During our recent studies on the potential influence of global warming on the evolution of proteins from influenza A virus [1][2][3][4][5], we noticed that the temperature fluctuates around the temperature trend. On the one hand, these fluctuations can be easily attributed to random effects; on the other hand, these fluctuations might imply that we might need a random model to describe the temperature pattern because the output of any deterministic model is generally a smooth curve.…”
Section: Introductionmentioning
confidence: 99%